Como os usuários de um centro de atenção psicossocial se ocupam da espiritualidade? - FIGUEIREDO, Marcella Oliveira (2023)
This study aims to understand how users of a Psychosocial Care Center (CAPS) occupy themselves with their spirituality. The research was developed in a CAPS I, located in Belém / Pa. Six users from CAPS I were enrolled in the study, all of which were over 18 years old, regularly attended by the center and agreed to participate, signing the Informed Consent Form (ICF). Data collection was performed through an interview, individualized to the research participants, and recorded in audio and transcribed later. For data analysis, Bardin content analysis was used. The results obtained showed that spirituality is often confused with religiosity. It was also revealed that spirituality and/or religiosity play an important role to the health of users, regardless of the perception and performance of their activities. The study emphasizes the importance of spirituality and / or religiosity in human occupation, compression of the subjectivity of users in the participation of their activities, addressing it in order to promote wellbeing, health and quality of life to the user.